1930
DOI: 10.1152/ajplegacy.1930.95.3.681
|View full text |Cite
|
Sign up to set email alerts
|

The Nervous Control of Respiration in Kittens

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1950
1950
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…2001). Evidence suggests that vagal innervation of the lung plays a key role in this vital process and several studies have shown that postnatal vagal denervation produces deleterious effects on ventilation as well as breathing patterns during the new- (Coombs &Pike, 1930;Schwieler, 1968;Fedorko et al 1988). This communication discusses the role of vagal innervation (a) in modulating the fetal breathing movements, (b) in establishing breathing during transition from the fetal to the neonatal period and (c) during the early neonatal period.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…2001). Evidence suggests that vagal innervation of the lung plays a key role in this vital process and several studies have shown that postnatal vagal denervation produces deleterious effects on ventilation as well as breathing patterns during the new- (Coombs &Pike, 1930;Schwieler, 1968;Fedorko et al 1988). This communication discusses the role of vagal innervation (a) in modulating the fetal breathing movements, (b) in establishing breathing during transition from the fetal to the neonatal period and (c) during the early neonatal period.…”
Section: Introductionmentioning
confidence: 95%
“…To date, very few studies have investigated the role of vagal innewation on neonatal control of breathing; however, these studies have consistently shown that vagal innervation plays a more important role in the control of breathing in newborns as compared with adults (Coombs & Pike, 1930;Schwieler, 1968;Duron & Marlot, 1980;Fedorko et al 1988;Delacourt et al 1995). Coonibs & Pike (1930) examined the effects of cervical vagotomy in anaesthetised, tracheotomised kittens.…”
Section: Vagal Innervation and Neonatal Control Of Breathing Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to whieh postal respiration eoinpcii'<!ites for the removal of (liajihragmatie activity is iiicoiistant (Gcscll and Mover,193]), but is in part related to the age of the expei-imental yiiinial. In young animals, where vsigotomy stops the 'liaphrapm, the thoracic inusculatuic does not adeqnately compensate until this sensitivity to vagotomy is lost with increaaintr u^c (Coombs and Pike, 1930). Simitar observations tliMt vagotomy may stop respiration have been made by Kcippiinyi aii'l Kleitman (19-7).…”
Section: The Organization Of the Central Respiratory Mecha/nismmentioning
confidence: 99%
“…At birth, the nervous control of breathing appears immature in animals (Coombs and Pike, 1930) as well as in man (Dawes and Mott, 1959), and is all the more so when the function is studied during sleep (Monod and Pajot, 1965;Dreyfus-Brisac, 1970;Finer et ai, 1976). The present histological study aims at delineat ing how immature the peripheral part of the control system of breathing is and how much this state contributes to the neonatal immatu rity of the nervous control of respiration in the 1 Attaché dc Recherche à l'lnserm.…”
Section: Introductionmentioning
confidence: 99%